Non-Performing Loans in the ECCU : Determinants and Macroeconomic Impact - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2016)
This paper assesses the determinants of NPLs in the Eastern Caribbean Currency Union (ECCU) and whether a deterioration in asset quality may result in negative feedback effects from the banking system to economic activity. The results suggest that the deterioration in asset quality can be attributed to both macroeconomic and bank-specific factors. Banks with stronger profitability and lower exposure to the construction sector and household loans tend to have lower NPLs. Further, some evidence indicates that foreign owned banks systematically have lower NPLs than domestic banks, pointing to the presence of important differences across bank practices with an impact on asset quality. Finally, the results emphasize the strength of macrofinancial feedback loops in the ECCU.